The impact of changes in regulatory and market environment on sustainability of wine producers: A structural equation model - Chinedu Obi; Daniele Vergamini; Fabio Bartolini; Gianluca Brunori (Wine Economics and Policy, 2020)
We explore the farmers' perception of how different external drivers of changes in farming activities could lead to sustainability practices among wine producers. The general assumption is that regulatory and market forces can change the production strategies of wine producers, which could eventually lead to the adoption of sustainability practices. We presented the percentage sustainability practice (PSP) as a novel way of measuring sustainability. We developed a structural equation model (SEM) with 13 hypotheses to test our assumption for the wine supply chain in Tuscany (Italy). Among the market forces, we found that wine growers perceived access to credit to have a significant positive association with sustainability practices. We also found that the perception of change in regulatory instruments such as environmental regulation and Common Agriculture Policy can lead to sustainable practice if they improve access to credit. Our research provides evidence for medium-large scale wine producers, emphasising their role as carriers of innovation in the movement towards sustainable wine production.
Keywords: 330; sustainability; wine; Structural Equation Model